2018
DOI: 10.1590/s1413-41522018165852
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação geoquímica de metais em sistemas fluviais afetados por atividades antrópicas no Quadrilátero Ferrífero

Abstract: RESUMO O presente estudo foi realizado na bacia hidrográfica do Rio do Peixe, Quadrilátero Ferrífero (QF), em Minas Gerais. Essa bacia apresenta um cenário geológico distinto e atividades antrópicas diversificadas, como a mineração de ferro, ouro e gemas, a agropecuária e a silvicultura. O principal objetivo desta pesquisa foi investigar as possíveis fontes de contribuições antropogênicas dos metais em sedimentos de fundo. Para isso, foram realizadas duas campanhas com amostragens de sedimentos de fundo em 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
6
0
7
Order By: Relevance
“…The occurrence of iron in the Rio do Peixe watershed is due to local geology, since iron-rich rocks are typical in the IQ. However, these elevated values exhibited a direct relationship with the tailings retention and the practice of iron ore beneficiation that have been taking place in the Rio do Peixe (Nascimento et al, 2018). Iron concentrations in the bottom sediments of the Rio do Peixe exhibit a direct relationship with the IQ geology and with anthropogenic activities.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The occurrence of iron in the Rio do Peixe watershed is due to local geology, since iron-rich rocks are typical in the IQ. However, these elevated values exhibited a direct relationship with the tailings retention and the practice of iron ore beneficiation that have been taking place in the Rio do Peixe (Nascimento et al, 2018). Iron concentrations in the bottom sediments of the Rio do Peixe exhibit a direct relationship with the IQ geology and with anthropogenic activities.…”
Section: Resultsmentioning
confidence: 93%
“…Studies in the Iron Quadrangle also found an increase of solids during the rainy season and differences in the seasons were due to impacts of mining activity (Raposo et al, 2011;Parra et al, 2012). While in urban industrial (mining operation) areas, the high turbidity values for the different seasons of the year were directly associated with the residues escaping from the dams and containment basin of the mining companies located upstream of the stations (Nascimento et al, 2018). Particularly, sampling station P2 experienced more mining influences, hence it showed high turbidity values: 1281 NTU in the rainy period and 990 NTU in the dry season.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Nesse sentido, estudos como os de Cesar et al (2012), Da Silva et al (2017), Nascimento et al (2018 e Dos Reis et al (2020), sob o viés de análise de indicadores geoquímicos, oferecem importantes contribuições para a identificação e rastreamento de fontes de contaminação antropogênicas e determinação de concentrações de elementos-traço. Assim, mostra-se necessário o conhecimento de técnicas acerca de identificação de teores de elementos-traço para estudos ambientais em sistemas fluviais, via rastreamento de fontes de origem geogênica e/ou antropogênica para avaliação da dinâmica de poluição e destinação de uso da terra em áreas urbanas.…”
Section: Introductionunclassified